Tylvalosin administration in pregnant sows attenuates the enlargement and bluish coloration of inguinal lymph nodes in newborn piglets. (August 2019) - Zhang, Lili; Li, Zhiyao; Deng, Xiaohong; Li, Jiansheng; Li, Taomei; Lv, Yingjun
Abstract: In the porcine industry, some piglets show slightly enlarged and bluish inguinal lymph nodes. However, the causative factors for these signs and prevention of these signs remain unclear. Tylvalosin is a broad-spectrum antibiotic with an immunomodulatory function. This study was aimed at evaluating the effect of tylvalosin on the abovementioned signs. Thus, fifteen 90-day pregnant sows were divided into an untreated control group and 0.1 and 0.2 g/kg feed tylvalosin-treated groups until delivery. Forty-five piglets on day 2 after birth (15 each group) were blooded, then oxidative stress, serum cytokine levels, routine blood analysis, and effect of sera on macrophage phagocytic activity were examined. Fifteen piglets on day 2 after birth (5 in each group) were euthanized and pathological changes in the inguinal lymph nodes were observed. The untreated piglets showed hemorrhage, hemosiderin accumulation, and increased macrophages in the inguinal lymph nodes. However, tylvalosin administration in sows alleviated these signs in their piglets; increased total antioxidant capacity and serum glutathione levels; decreased serum IL-1β, TNF-α, and IL-10 levels; improved the percentages of neutrophils and lymphocytes in the blood; and increased the body weight of the weaning piglets. In addition, the serum of newborn piglets also showed enhanced RAW264.7 macrophage phagocytic activity. These results demonstrated that tylvalosin administration in pregnant sows attenuates the enlargement and bluish coloration of inguinal lymph nodes in newborn piglets. Highlights: Enlarged and bluish lymph nodes is relate to hemorrhage and hemosiderin accumulation. Administration of tylvalosin is beneficial for attenuating these signs. Administration of tylvalosin increases antioxidative activity. Administration of tylvalosin increases macrophage phagocytic activity. Administration of tylvalosin decreases pro-inflammatory cytokine levels.